Dampak Variabel Moneter Amerika Serikat terhadap Stabilitas Perekonomian Indonesia - Okto Riyo Ananda; Idris (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to examine the extent of the influence of United States monetary policy on the stability of the Indonesian economy. The data used is time series data from 2012 to 2022. This research uses simultaneous equation analysis with the two stage least squares (2SLS) method. The research results show that simultaneously the Fed interest rate variables and United States inflation have a significant influence on the exchange rate in Indonesia. Apart from that, the Fed’s interest rates, United States inflation and the exchange rate (KURS) also have a significant influence on the stability of the Indonesian economy.